9=3-4x+6x

Simple and best practice solution for 9=3-4x+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=3-4x+6x equation:


Simplifying
9 = 3 + -4x + 6x

Combine like terms: -4x + 6x = 2x
9 = 3 + 2x

Solving
9 = 3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
9 + -2x = 3 + 2x + -2x

Combine like terms: 2x + -2x = 0
9 + -2x = 3 + 0
9 + -2x = 3

Add '-9' to each side of the equation.
9 + -9 + -2x = 3 + -9

Combine like terms: 9 + -9 = 0
0 + -2x = 3 + -9
-2x = 3 + -9

Combine like terms: 3 + -9 = -6
-2x = -6

Divide each side by '-2'.
x = 3

Simplifying
x = 3

You can always share this solution

See similar equations:

| -3(5t+9)= | | 3(x+4)*2=7 | | 2x+b=3c | | 5x-8=-2(x+4)-28 | | 6(x-5)+1=3x-2 | | -8w+17-w=-2(3w+1) | | 2(3x-2)+5=25 | | 14x+4=-7x+25 | | 2x+3=12x-12 | | 6x+4=3x+(-2) | | -(5x-12)+3(4x+4)= | | 2x^3+3x^2+8x-5=0 | | -6(x+1)-10=19+7 | | 9-5.9= | | 7sinx+7=0 | | 3-(2x+5)=-2(4x+1) | | 5w+4=44-3w | | 203=7(8+7p) | | 3c^2+14c-38=0 | | 9-3y=4y+30 | | 10y+24-(-11y)+30=0 | | 4(3a-8)=-11a | | 3x^4-8x^3-2x^2+7x-2=0 | | 6w-9w=24 | | -1=4-4 | | -24+(-23)= | | 2=11-3 | | n+(n+1)+(n+2)-(n+1)=50 | | 10=10-3x | | 81x^4+27x^3+9x^2+3x-2=130 | | x(5x-4)(x+3)= | | 78-6t=18 |

Equations solver categories